Respostas locais no enfrentamento da pandemia de COVID-19: o caso da atenção primária à saúde em Campo Grande/MS - Cruz, Joyce Alves da (2022)
As of 2019 the novel Coronavirus emerged and quickly initiated a pandemic that has caused many concerns in the world. At first, knowledge about this disease was scarce and as it was happening, fake news and beliefs about the disease multiplied. The World Health Organization has issued warnings about the severity of SARS-CoV-2 and the need for interventions. Even so, several layers of predicament settled in the territories, causing impacts on health and other social aspects, quality of life and production of life. Thus, it is very important to look at the local initiative in order to understand this context. There was no national coping strategy in Brazil, the responsibilities have been designated to states and municipalities, which generated several little-known responses. To this end, this study analyzed responses in several territories and in Campo Grande-MS as the pandemic was being fought against, and its influence on the services and life of the population. It was based on documental analysis, being carried out with documents and data from the public databases, developed in four stages. The first, an integrative literature review describing international responses in the first wave of the pandemic. In the second and third, epidemiological indicators and initiatives were analyzed and compared, with emphasis on Campo Grande-MS and Primary Health Care. In the fourth, a cartographic approach centered on the experience of the master's student. The result of the first stage brought together experiences with important lessons from the countries analyzed, with more assertive, immediate and rigorous responses in pandemic control. In the second and third stage, at the local level, the findings indicate oscillations in the indicators during 2020 until July, 2021. In the municipality, there were 126,657 infected, with a majority in people aged 30 to 39 years (29,704) and women (55% - 68,659). There were 3,707 deaths, with high mortality in males (55%) and in the elderly over 60 years (2,417 deaths). In the state, 31% (2,791) of the cases of deaths had at least one comorbidity, such as cardiovascular disease (42.4% - 3,785). With the emergence of variants (march, 2021), there was an increase in ICU hospitalization (98%), falling to 58% in July 2021, after the advance of immunizations. The initial interventions indicate that strict measures of spatial isolation associated with collective sense were paramount to contain the progress of the disease. However, the feeling of control of the pandemic in the months analyzed in 2021 and in the face of the emergence of variants associated with insufficient initiatives, caused a scenario of collapse in hospitals and increased mortality. These findings convey important lessons that must not be ignored, calling for further studies, especially of improvement along the path of the pandemic. He concluded that the commitment among decision makers, primary health care with the advancement of science, is imperative to face the pandemic and needs to be strengthened in order to overcome the next challenges. The research generated technoscientific publications that were made available in books and presentation in national and international congresses. Finally, the course of the research that underpins the dissertation, systematized in the format of technology the formation in collective health provided by the master's degree.